History of Mathematics in Nepal - B.C., Gopal (Academic Journal of Mathematics Education, 2021)
Nepal is one of the nations of South Asia, which is situated in the southern part of the Himalayan region. In retrospect, the ancient history of South Asian subcontinent reveals that it consisted of many kingdoms for several centuries of its history. The later geo-political subdivision of the subcontinent consists of eight nations, and these nations are coordinated by the institution of SAARC established in 1985AD (Schaaf, 1975). Modern India covers major part of the subcontinent. Obviously, the ancient India has influenced the religions, culture, costumes, social practices, etc. of other nations of the subcontinent.